Trade Policy and the Household Distribution of Income - J. Francois; H. Rojas-Romagosa (Tinbergen Institute, 2004)
We explore the relationship between import protection and the household distribution of income. We first develop a general-equilibrium mapping from tariffs to household inequality measures. This also yields predictions for linkages between tariffs, development level, and observed household inequality. Working with a new dataset, we then examine crosscountry variation in inequality with respect to import protection. Results are consistent with predictions of the factor-intensity model of trade. Regression results suggest that import protection makes income distribution worse for countries in labor-intensive diversification cones. This relationship shifts to one of falling inequality as incomes rise and we move to capital-intensive diversification cones.
Keywords: F13; D31; O15; 330; trade; inequality; distribution of income; Atkinson index; Gini coefficient; globalization; tariffs; Protektionismus; Einkommensverteilung; Zoll; Disparitätsmaß